KEPUASAN KERJA SEBAGAI PEMEDIASI PENGARUH KARAKTERISTIK PEKERJAAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL - Ratih Dwi Arini; Euis Soliha (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
The purpose of this study is to analyze the effect of job characteristics and motivation on organizational commitment with job satisfaction as mediation. Population used Account Representative (AR) officer in Regional Office of Directorate General of Taxes (DJP) of Central Java I, which numbered 175 employees. Sample taken 122 employees. Types of data used primary data and data collection methods kuesionier. The analysis technique used path analysis. The results showed that: 1. Job characteristic effect on job satisfaction. 2. Motivation effect on job satisfaction. 3. Job characteristic effect on organizational commitment. 4. Motivation effect on organizational commitment. 5. Job satisfaction effect on organizational commitment. 6. Job satisfaction mediates between job characteristics on organizational commitment. 7. Job satisfaction mediates between motivation on organizational commitment.